Kebangkrutan Perusahaan dalam Prespektif Undang-Undang Nomor 37 Tahun 2004 Tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang - Tatu Afifah (Faculty of Social, Politic, and Law Science, Universitas Serang Raya, 2025)
This journal examines corporate bankruptcy from the perspective of bankruptcy law, where a bankrupt company does not mean that the company is bankrupt. Because bankruptcy is an economic status, while bankruptcy is a legal status. If a bankrupt company has the status of bankruptcy, it must submit an application to the commercial court to obtain a bankruptcy decision. This study aims to determine the mechanism for handling a bankrupt company and the authority of a bankrupt company over the assets owned by the company. This study uses a qualitative approach with a descriptive-analytical method to analyze corporate bankruptcy against the economy from a legal perspective. The results of the study show that corporate bankruptcy shows an economic status, while obtaining legal status requires a commercial court decision with the status of becoming a bankrupt company. The authority of a bankrupt company over its assets is only limited to increasing the company's profits or assets. Keywords: Bankrupt; Insolvency; Company; Commercial Court.